MODERN FEATURES OF ENTERPRISE PERSONNEL DEVELOPMENT - Застрожнікова, Ірина (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2022)
The article is devoted to the study of the process of the hotel and tourism sector employees development in Ukraine. It is determined that the main elements of the personnel development system of hotel and tourism enterprises are its training, professional adaptation, career advancement, planning and management, work with personnel reserve, work behavior motivation, evaluation of staff work (including staff certification and evaluation of candidates for the vacant position). It is indicated that one of the human resources components in the hotel and tourism sector is education. As practice shows, in today’s world most employees of hotel staff and tourism companies in the country do not have special education, the skills to work with modern technology and approach to work in hotels and travel agencies, or knowledge of psychology and ethics of working with guests. The main stages of the training staff process in hotel and tourist service enterprises are generalized. The importance of professional adaptation and motivation is emphasised. There are two areas of professional adaptation: primary, adaptation of young employees who do not have professional experience (usually graduates), secondary, adaptation of employees with professional experience and change the object of activity or their professional role. In modern conditions, the construction of a motivation system +should be based on the following components: a system of personal and team responsibility, which provides the direction of employees’ efforts to achieve the strategic goals of the organization; a system of material motivation that allows you to manage the satisfaction of material needs of employees; system of intangible motivation, aimed at managing the satisfaction of staff needs for training, professional and career growth. The tasks that are solved in the planning and managing a business career process are summarized. The personnel development system should prioritize not only the task of professional development and retraining, but also the formation of a common culture within the organization, developing common quality standards, creating a personnel reserve, preventing loss of knowledge and breaking the technological chain in training, retaining valuable employees through qualified motivation system.